Serum N‐Terminal Pro‐B‐Type Natriuretic Peptide Is Associated With Insulin Resistance in Chinese: Danyang Study - Ziwen Zheng; Junya Liang; Yun Gao; Mulian Hua; Siqi Zhang; Ming Liu; Zhuyuan Fang (The Journal of Clinical Hypertension)
ABSTRACT The association of serum N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) with insulin resistance (IR), as measured by homeostasis model assessment of insulin resistance (HOMA‐IR), in the general population is unclear. Our study aimed to characterize its relationship in a large community‐based population. Subjects were recruited from the Danyang city between 2017 and 2019. Serum NT‐proBNP was measured using an enhanced chemiluminescence immunoassay. IR was defined by a HOMA‐IR in the highest sex‐specific quartile. Categorical and continuous analyses were performed with sex‐specific NT‐proBNP tertiles and naturally logarithmically transformed NT‐proBNP (lnNTproBNP), respectively. The 2945 participants (mean age 52.8 years) included 1728 (58.7%) women, 1167 (39.6%) hypertensive patients, 269 (9.1%) diabetic patients, and 736 (25.0%) patients with IR. In simple and multivariate‐adjusted regression analyses, serum lnNTproBNP were both negatively associated with HOMA‐IR (β = −0.19 to −0.25; p < 0.0001). Similar results were also obtained in multiple subgroup analyses. In multiple logistic regression analyses, elevated serum NT‐proBNP was associated with lower risks of IR (odds ratios: 0.68 and 0.39; 95% confidence intervals: 0.61–0.74 and 0.30–0.50 for lnNTproBNP and top vs. bottom tertiles, respectively; p < 0.0001). In conclusion, increased serum NT‐proBNP level was strongly associated with a lower risk of IR in Chinese.